Multiple itchy nodules over the scalp - clinicopathological challenge - Aditi Dhanta; Gargi Taneja; Neirita Hazarika; Michael Leonald Anthony (Wolters Kluwer Medknow Publications, 2021)
Angiolymphoid hyperplasia with eosinophilia is an uncommon benign vascular proliferation with histologically distinct endothelial cells and a mixed inflammatory infiltrate composed of mainly lymphocytes and eosinophils unknown. It commonly affects middle-aged adults and characterized by flesh/plum-colored pruritic nodules and papules. In our case, it has to be differentiated from other appendageal tumors such as cylindroma, spiradenoma because of similar site involvement. The histopathological examination is a fundamental tool to achieve a correct diagnosis.